Nonpolar and semipolar ultraviolet multiple quantum wells on GaN/sapphire. (15th March 2019) - Fan, Xiaomeng; Xu, Shengrui; Li, Peixian; Zhang, Jincheng; Peng, Ruoshi; Zhao, Ying; Du, Jinjuan; Hao, Yue
Abstract: The surface morphologies, anisotropic quality and optical properties of nonpolar and semipolar ultraviolet multiple quantum wells (MQWs) structures on GaN/sapphire deposited by metal organic chemical vapor deposition are investigated. The crystal planes of the MQWs are identified as nonpolar (11 2 ¯ 0) plane and semipolar (11 2 ¯ 2) plane by the 2θ−ω scan of high-resolution X-ray diffraction (HRXRD). The results of the atomic force microscope and scanning electron microscope show that the surface morphologies of nonpolar and semipolar MQWs structures have obvious differences. The X-ray rocking curves of nonpolar and semipolar MQWs on-axis diffraction planes by HRXRD demonstrate that the semipolar MQWs structure has a better crystalline quality and a weaker anisotropy of crystal quality than nonpolar MQWs structure. The temperature dependence photoluminescence (PL) spectra reveal that the nonpolar MQWs structure have a stronger yellow band than semipolar MQWs structure. Besides that, the PL spectra of nonpolar MQWs structure also show a blue-shift as temperature increases within a certain range, and then, when the temperature increases continuously, it turns to a red-shift. However, for the semipolar MQWs structure, only the red-shift is observed in PL spectra.